MANAJEMEN PENDIDIKAN ANAK DALAM KELUARGA - Aimi, Aimi (Jurnal Ecoment Global, 2019)
The concept of Child Education Management according to the Qur'an". The Qur'an is a revelation of God which was revealed to Prophet Muhammad as the eternal miracle of all time. The Qur'an is the Holy Book of the Muslims which contains guidelines for a happy life and guidance of the world and the hereafter. It contains worship, morals, exemplary story, occult news, universe and so on. Even the Qur'an mentions that It also functioned as an explanation of all things (tibyanan likulli sya-in) (QS. An Nahl/16:89). This reaffirms that there is no exception, everything in the universe hasits explanation from the Holy Qur'an. No exception regarding family issues, especially related to parenting and education for children who grew up in his family environment. The main problems in this research is how is the concept of child education management according to the Qur'an in thefamily? In line with that, the Holy Qur'an encourage every parent to feel worried, if then behind the day after, they left a weak generation (QS. An Nisa '/4:9). This is the requirement so that each moslem parent are able to manage their children's education so they can grow and develop a independently. For that, it needs a pattern and attempts so that the process can go as desired. The method used in the writing of this thesis is the method of thematic tafseer (maudhu'i). And the purpose of the research is to be able to find the concept of child education management in a family that Qur'anic. Ultimately it is hoped that the concept of child education management within the family based on the Qur'an will be the solution to achieve the goals of parents to have pleasant children (QS. Al Furqan/25:74), starting with the planning (planning) (QS. Al Anfal/8:60),organizations (organizing) (QS. Ash Shaff/61:4), applications (actuiting) (QS. At-Tawba: 105/9) and control (controlling) (QS. QAF/50:16-18). The four stages above, are big agendas for each moslem family in order for their children to become shalih and shalihah. Good cooperation between husband and wife in dividing duties and obligations as a father and mother became the key word in determining the success of the process of upbringing and education of their children to become a perfect human being as they expectedÂ Keyword :Â management, education, child, family